2005
DOI: 10.1614/wt-04-188
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pyrithiobac Application Rate and Timing on Weed Control and Cotton Yield in Greece1

Abstract: Field experiments were conducted at four locations (Larissa, Halkidona, Thessaloniki, and Halastra) in Greece to evaluate weed and cotton response to various pyrithiobac rates applied preplant incorporated (PPI), preemergence (PRE), or postemergence (POST). Pyrithiobac applied PPI or PRE at 0.068, 0.102, or 0.136 kg ai/ha controlled black nightshade, pigweeds, and common purslane at Larissa. However, pyrithiobac applied PRE at Thessaloniki and Halkidona was more effective against black nightshade and pigweeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…Several studies have reported that the residual phytotoxic activity of soil‐applied herbicides primarily coincided well with the amount of herbicides in the soil, such as atrazine (6‐chloro‐ N ‐ethyl‐ N′ ‐[1‐methylethyl]‐1,3,5‐triazine‐2,4‐diamine; Aladesanwa 2005), imazamox (2‐[4,5‐dihydro‐4‐methyl‐4‐(1‐methylethyl)‐5‐oxo‐1 H ‐ imidazol‐2‐yl]‐5‐[methoxymethyl]‐3‐pyridinecarboxylic acid; Bresnahan et al . 2002), isoxaben ( N ‐[3‐(1‐ethyl‐1‐methylpropyl)‐5‐isoxazolyl]‐2,6‐dimethoxybenzamide; Chandran & Derr 1998) and pyrithiobac (2‐chloro‐6‐[(4,6‐dimethoxy‐2‐pyrimidinyl) thio] benzoic acid; Kaloumenos et al . 2005), and imazethapyr (2‐[4,5‐dihydro‐4‐methyl‐4‐(1‐methylethyl)‐5‐oxo‐1 H ‐imidazol‐2‐yl]‐5‐ethyl‐3‐pyridinecarboxylic acid; Ayeni et al .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that the residual phytotoxic activity of soil‐applied herbicides primarily coincided well with the amount of herbicides in the soil, such as atrazine (6‐chloro‐ N ‐ethyl‐ N′ ‐[1‐methylethyl]‐1,3,5‐triazine‐2,4‐diamine; Aladesanwa 2005), imazamox (2‐[4,5‐dihydro‐4‐methyl‐4‐(1‐methylethyl)‐5‐oxo‐1 H ‐ imidazol‐2‐yl]‐5‐[methoxymethyl]‐3‐pyridinecarboxylic acid; Bresnahan et al . 2002), isoxaben ( N ‐[3‐(1‐ethyl‐1‐methylpropyl)‐5‐isoxazolyl]‐2,6‐dimethoxybenzamide; Chandran & Derr 1998) and pyrithiobac (2‐chloro‐6‐[(4,6‐dimethoxy‐2‐pyrimidinyl) thio] benzoic acid; Kaloumenos et al . 2005), and imazethapyr (2‐[4,5‐dihydro‐4‐methyl‐4‐(1‐methylethyl)‐5‐oxo‐1 H ‐imidazol‐2‐yl]‐5‐ethyl‐3‐pyridinecarboxylic acid; Ayeni et al .…”
Section: Introductionmentioning
confidence: 99%
“…2006). Also, Kaloumenos et al . (2005) found that pyrithiobac provided excellent control of black nightshade and redroot pigweed.…”
Section: Resultsmentioning
confidence: 89%
“…2005). However, pyrithiobac provides poor control of some economically important broad‐leaved weeds, like common lambsquarters ( Chenopodium album L.) and tall morningglory ( Ipomoea purpurea L. Roth) (Culpepper & York 1998; Kaloumenos et al . 2005), while trifloxysulfuron‐sodium provides poor control of velvetleaf ( Abutilon theophrasti Medik.…”
Section: Introductionmentioning
confidence: 99%
“…Cotton plants show signs of damage after application of the herbicide, but they recover after 30 -40 days. In Greece the effect of different doses of pyrithiobac-sodium on weeds and cotton was studied (Kaloumenos, 2005). Ryrithiobacsodium was applied at different periods: before sowing by incorporation, after sowing before emergence, and during the growing season of cotton.…”
Section: Weed Control In Cottonmentioning
confidence: 99%